2020
DOI: 10.21037/med.2019.10.01
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring surgical quality: the cumulative sum (CUSUM) approach

Abstract: Monitoring the quality of new or ongoing surgical activities is a necessity. Several Statistical Process Control (SPC) tools are available to professionals. Among them, Shewhart charts and cumulative sum charts (CUSUM charts) are useful methods to provide visual feedback before significant quality issues arise. In this paper, we discuss both methods based on our current approach. On Shewhart charts, one variable value is plotted on a time-series line. This method provides information about every single determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“… 22 , 23 A previous study reported that an HIFU ablation of uterine fibroids that achieved an immediate NPVR of at least 80% was safe. 14 Recently, researchers have set the NPVR at a minimum of 80% as a measure of sufficient ablation in the HIFU ablation therapy of uterine fibroids. 25 , 26 Even some researchers have shown that an NPVR of 90% can be used as a standard for the HIFU ablation therapy of uterine fibroids.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 22 , 23 A previous study reported that an HIFU ablation of uterine fibroids that achieved an immediate NPVR of at least 80% was safe. 14 Recently, researchers have set the NPVR at a minimum of 80% as a measure of sufficient ablation in the HIFU ablation therapy of uterine fibroids. 25 , 26 Even some researchers have shown that an NPVR of 90% can be used as a standard for the HIFU ablation therapy of uterine fibroids.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The cumulative recurrence rate in 2 years was less than 10% when 70% of NPVR was achieved, which was similar to that of myomectomy. 13,14 Recently, with the increasing clinical application of HIFU technology, the effectiveness of NPVR ! 80% and NPVR !…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations